2014
DOI: 10.1002/chem.201304680
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic–Organic Heteropolyacid–Gold(I) Hybrids: Structures and Catalytic Applications

Abstract: Gold(I)-polyoxometalate hybrid complexes 1-4 ([PPh3AuMeCN]xH4-x SiW12O40, x=1-4) were synthesized and characterized. The structure of the primary gold(I)-polyoxometalate 1 (x=1) was fully ascertained by XRD, FTIR, (31)P and (29)Si magic-angle spinning (MAS) NMR, mass spectroscopy, and SEM-energy dispersive X-ray spectroscopy (EDX) techniques. Moreover, this complex exhibited better catalytic activity and selectivity compared with standard, homogeneous, gold catalysts in the new rearrangement of propargylic gem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 64 publications
0
28
0
Order By: Relevance
“…Indeed, POMs are polyanionic molecularly defined clusters of early transition metals and oxygen 1. They are thus suitable ligands for transition metals,2 or supports for active species in heterogeneous catalysis, for example, Lewis acidic cations2b, 3 or organic chiral acids 4. Of particular interest are the reports by the Neumann group, in which a redox active POM supports a metal catalyst by electrostatic interactions and leads to cooperative catalysis 5…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, POMs are polyanionic molecularly defined clusters of early transition metals and oxygen 1. They are thus suitable ligands for transition metals,2 or supports for active species in heterogeneous catalysis, for example, Lewis acidic cations2b, 3 or organic chiral acids 4. Of particular interest are the reports by the Neumann group, in which a redox active POM supports a metal catalyst by electrostatic interactions and leads to cooperative catalysis 5…”
Section: Methodsmentioning
confidence: 99%
“…10 In this area, we have recently demonstrated that gold(I) cations were effectively very good candidates in constructing type III organic−inorganic complexes. 11,12 Moreover, depending on the applied stoichiometry (x, Scheme 1), excellent and new gold reactivities have been obtained using such [(Ligand)Gold(I)-(Solvent)] +…”
Section: ■ Introductionmentioning
confidence: 99%
“…Reported gold POM compounds made from inorganic gold salts often display limited stability with undesired reduction into gold nanoparticles . Recently, Nomiya and our group have described two series of redox stable gold(I)‐phosphane POM hybrid materials (type III) made with the cationic [Au(PPh 3 )(MeCN) + ] fragment or the [{Au(PPh 3 )} 4 ( μ 4 ‐O) [2]+ ] cluster .…”
Section: Introductionmentioning
confidence: 99%